Google Translate as a Learning Tool Assistance for Non-English Departments Students: Student Perspectives - Rakhmanina, Lisa; Melati, Melati; Marita, Yosi; Masitah , Siti (Edu-Ling: Journal of English Education and Linguistics, 2024)
The purpose of this study is to determine students' views of Google Translate in English learning. The key challenge of this study is how do students perceive Google Translate as a translation tool in the online English learning process? Ten undergraduate students from Non-English department students at Universitas Prof Dr Hazairin SH were selected as research participants. The instruments used were questionnaire and interview. The current research attempts to address the distinction by investigating the manner in which Google translates support for non-English department students in learning English from the perspective of the students. Even though there are numerous drawbacks to employing Google Translate, students continue to perceive it as having more benefits than drawbacks. In addition to numerous benefits, the findings also indicated that Google Translate still encounters difficulties, such as inaccurate translations of the learner's intended meaning. Another finding indicated that in order to get improved translation, it is necessary to utilize online machine translation, particularly when translating lengthy sentences.  It may be inferred that the Google translation tool can be selected as the primary supplementary learning tool, especially for learning English.